The Impact of Age on Treatment Responses in Patients with Non-Small Cell Lung Cancer Treated with Immune Checkpoint Inhibitors - Gülin Alkan Şen; Hande Turna (Cerrahpaşa Medical Journal)
Objective: The correlation between age and the incidence and prevalence of cancer is well-established. Immunosenescence is thought to be underlying this condition. This retrospective research aimed to investigate the impact of aging on the responses to immune checkpoint inhibitor (ICIs) treatment responses in advanced non-small cell lung cancer (NSCLC) patients.